Trabalho infantojuvenil em feiras de Aracaju/SE : uma análise a partir da ação civil pública 0000820-19.2012.5.20.0001 - Nascimento, Marcelo Oliveira do (2019)
The exploitation of child labor is a social fact that brutally violates the fundamental rights of children and adolescents. Currently, it is a problem that affects many countries in the world. Therefore, it has been studied by Law and other branches of the Social, Human and Health Sciences. The work of infant and young people in this research can be understood as any and all habitual activity carried out by children and adolescents, with or without remuneration, that goes against the limits legal for the exercise of work, as well as depriving children and adolescents of enjoying their specific developmental condition. However, in the past, it was seen as something natural and it was even encouraged depending on the cultural disposition. Looking back at the history of labor of children under eighteen years old in Brazil, we can observe the practice of labor activities since the colonization period. The construction of childhood, an idea conceived in the Modern age, determines the incentive of a historical evolution of the expansion of fundamental rights and guarantees of children and adolescents worldwide. In Brazil, the first step of the promotion is made after the Federal Constitution of 1988 and the Statute of the Child and the Adolescent, in 1990. However, even with the whole apparatus of Brazilian legislation, with emphasis on the Doctrine of Integral Protection, children and adolescents still suffer from labor exploitation, which is presented explicitly or in more naturalized way, for exemple, such as child and youth labor in street markets. This is exactly the focus of the present study, taking as a scenario the city of Aracaju. The object of analysis is the public civil action 0000820-19.2012.5.20.0001 and its developments, which resulted in the city being sentenced to pay compensation for collective moral damages and the obligation to promote actions in order to tackled the problem. It is discussed the impact and reach of the public civil action as a sufficient instrument to solve the problem of child labor in the street markets of Aracaju/SE, that produce the maintenance of a cycle of poverty and marginalization that plagues such children, adolescents and their families. This analysis uses the hypothetical-deductive method, with the help of case study techniques and bibliographic review in qualitative and exploratory research.